The study of coloronyms in psycholinguistic aspect - Pak, M.K.; Tugambekova, D.T. (KSU Publ., 2017)
The article is devoted to the problems of study of the nominative units with the semantics of colour in psycholinguistic aspect. The overview of linguistic research of coloronyms is carried out in the work, psycholinguistic features of colour names and the significance of colour meanings are identified in the framework of the psycholinguistic aspect. The words which specify colour, its semantic features are analyzed, the system of colour vocabulary is classified and the issues associated with reflection of colour categories in human consciousness are described.
Колоронимдерді психолингвистикалық тұрғыда зерттеу
Исследование колоронимов в психолингвистическом аспекте
Keywords: colour names; coloronym; psycholinguistics; colour perception; semantics; colourcategorization; colour system